Metabolic syndrome and the associated risk factors in Iranian adults: A systematic review - Karimollah Hajian-Tilaki (Babol University of Medical Sciences, 2015)
Background: Metabolic syndrome (MetS) is a complex clustering cardiovascular risk factors such as abdominal obesity, hypertension, diabetes and dyslipidemia. It has been a growing health problem in Iranian adults in recent decade. The objective of this article was to review the prevalence of MetS and the corresponding risk factors among Iranian adults.Methods: We conducted a systematic review to extract the published articles regarding metabolic syndrome and its risk factors among Iranian adults aged >19 years by searching in PubMed, Google Scholar, SID, Magiran and Iranmedex databases. The forty-three published articles were selected regarding MetS among Iranian adults in this review during 2005-2014.Results: From the 43 studies, the rate of MetS varied from 10% to 60% depending on sex, age and region. The highest rate reported among postmenopausal women in Shiraz was over 60%. There was almost a consistent finding that the rate of MetS was higher among women compared with men across national level except in one study. A very sharp difference (43.3% vs. 17.1%) was observed in western Iran (Kordestan province) between sexes. MetS was significantly more prevalent among older adults, postmenopausal women, less-educated people, those living in urban areas and those with low physical activity and unhealthy eating habits across national level consistently.Conclusion: An emerging high rate of MetS across national level highlights the lifestyle modification as preventive measures in Iranian population by focusing primarily on high risk profiles such as low socioeconomic background, low level of education, older age and postmenopausal women.